Integration of Shariah and Hakikat in the Tijaniyyah Tarekat: An Analysis of Global and Local Acceptance Through the Perspective of Mīzān al-Shar - Marwal, Muhammad Ilyas; Ilyas, Muhammad Fadhlirabby (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the integration of Sharia and Haqiqat within the Tarekat Tijaniyyah, a Sufi order founded by Shaykh Ahmad al-Tijani in the 18th century in Morocco. This order emphasizes the importance of harmony between the practice of Sharia (Islamic rituals and laws) and the understanding of Haqiqat (profound spiritual knowledge). The concept of Mīzān al-Sharʿ (Shari'a Scale) was introduced by Shaykh al-Tijani to ensure that every teaching of the order aligns with Islamic law. This study also discusses the global and local acceptance of the Tarekat Tijaniyyah, particularly in Indonesia, by highlighting the religious moderation present in Indonesian society. The Tarekat Tijaniyyah is well-received in Indonesia due to its non-exclusive teachings and its relevance to existing Sufi spiritual traditions. Additionally, Mīzān al-Sharʿ provides a sense of security for the followers of the order by ensuring that the teachings they receive do not conflict with the fundamental principles of Sharia, thereby strengthening their commitment to living a spiritual life that balances worldly concerns with the hereafter. Through an approach that harmonizes Sharia and reality, the Tijaniyyah Order remains relevant amidst contemporary social and religious dynamics, both globally and locally